What inspires design? [electronic resource] (Films Media Group, 2012)
#aWhere do designers get their ideas? How do the environment, culture, and history shape designers' outlooks? Can collaboration create an inspired design? How do inspiration and innovation relate to each other? Modern design, powered by new technology and production techniques, is pushing the limits of human ingenuity. This program allows viewers to explore the minds and methods of product designers to learn how to breathe life into a new idea.